Morphological and molecular analyses confirm the occurrence of two sympatric Lysmata shrimp (Crustacea, Decapoda) in the southwestern Atlantic - Alves, Douglas Fernandes Rodrigues; Lima, Daniel José Marcondes; Hirose, Gustavo Luis; Martinez, Pablo Ariel; Dolabella, Silvio Santana; de Paiva Barros-Alves, Samara (Zootaxa, 2018)
An integrative approach was used, combining morphological and molecular analyses, to provide the first report of Lysmata lipkei and L. vittata in Sergipe State, Brazil, and confirm that both species are invasive of the Atlantic Ocean. Lysmata shrimps were sampled in the estuary region of the Vaza-Barris river, Sergipe State, northeastern Brazil, and identified as L. lipkei (n = 8) and L. vittata (n = 20). To molecular phylogenetic analysis was used 16S DNA fragments, comparing 26 species of the Lysmata-Exhippolysmata clade and two species of the genus Merguia (outgroup). Phylogenetic analysis indicated the absence of consistent genetic divergence (p distance < 0.018) between specimens from Atlantic and Indo-Pacific oceans. We conclude that L. lipkei and L. vittata have successfully invaded the western Atlantic and are also present in Sergipe State, northeastern Brazil.